Recovery after Propofol Infusion Anaesthesia in Children: Comparison with Propofol, Thiopentone or Halothane Induction Followed by Halothane Maintenance - Aun, C. S. T. (Institutional Knowledge at Singapore Management University, 1994)
We have compared the recovery profiles of 163 healthy Chinese children after general anaesthesia for minor surgical procedures. Patients were allocated randomly to receive one of four anaesthetic techniques: propofol infusion for induction and maintenance using a pharmacokinetic model-controlled syringe pump set initially at a target concentration of 8 µg ml–1 and then adjusted according to clinical requirements; propofol 2.5–3.5 mg kg–1, thiopentone 4–5 mg kg–1 or 2–3% halothane for induction of anaesthesia followed by 1–2 % halothane for maintenance of anaesthesia. All oatients breathed a mixture of 70% nitrous oxide in oxygen through a laryngeal mask airway and received an appropriate regional anaesthetic block. Recovery was assessed using the time to achieve full Steward score, open eyes on command, orientation and the time required to complete a simple ouzzle. Recovery was slowest with the propofol infusion (mean 39.8 (SO 12.9) min when eyes opened on command). The recovery times were significantly shorter with the three other techniques (propofol bolus 21.9 (9.9) min, thiopentone 23.4 (11.3) min, halothane 20.1 (8.9) min), and the choice among these three methods had no significant influence on the recovery profile.